Loss of UCHL1 promotes age-related degenerative changes in the enteric nervous system - Coulombe, Josée; Gamage, Prasanna; Gray, Madison T.; Zhang, Mei; Tang, Matthew Y.; Woulfe, John; Saffrey, M. Jill; Gray, Douglas A. (Frontiers in Aging Neuroscience, 2014)
UCHL1 (ubiquitin carboxyterminal hydrolase 1) is a deubiquitinating enzyme that is particularly abundant in neurons. From studies of a spontaneous mutation arising in a mouse line it is clear that loss of function of UCHL1 generates profound degenerative changes in the central nervous system, and it is likely that a proteolytic deficit contributes to the pathology. Here these effects were found to be recapitulated in mice in which the Uchl1 gene had been inactivated by homologous recombination. In addition to the previously documented neuropathology associated with loss of UCHL1 function, axonal swellings were detected in the striatum. In agreement with previously reported findings the loss of UCHL1 function was accompanied by perturbations in ubiquitin pools, but glutathione levels were also significantly depleted in the brains of the knockout mice, suggesting that oxidative defense mechanisms may be doubly compromised. To determine if, in addition to its role in the central nervous system, UCHL1 function is also required for homeostasis of the enteric nervous system the gastrointestinal tract was analyzed in UCHL1 knockout mice. The mice displayed functional changes and morphological changes in gut neurons that preceded degenerative changes in the brain. The changes were qualitatively and quantitatively similar to those observed in wild type mice of much greater age, and strongly resemble changes reported for elderly humans. UCHL1 knockout mice should therefore serve as a useful model of gut aging.